Pengembangan Model Pembelajaran Hybrid untuk Meningkatkan Kemampuan Berbahasa Mahasiswa - Rusli, Sri Mulyani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop an effective hybrid learning model to improve students' language skills. The methodology used is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subject of this research is students of language study programs at universities who are involved in language learning. Subjects were selected by purposive sampling, namely students who participated in the language learning program and had the potential to benefit from the application of the hybrid model. The research instruments consisted of questionnaires, tests, observations, and interviews. Data analysis uses descriptive analysis and inferential analysis. The results of the study show that the hybrid learning model developed is effective in improving students' speaking, writing, reading, and listening skills.